New records of marine biodiversity in the Mediterranean Sea (April 2026) - ARGYRO ZENETOS; FARES NASSER ABD EL-GWAAD; AHMED MOHAMED AL-BEAK; MOUNA ANTIT; YACOPO BALDACCHINO; CLAUDIO BARRÍA; ILIJA ĆETKOVIĆ; MAURIZIO COSTA; FABIO CROCETTA; NIKOLA ĐORĐEVIĆ; AMANI FITORI; BELLA S. GALIL; et al. (Mediterranean Marine Science, 2026)
This collective article presents new information about 18 species occurring in 12 Mediterranean countries from the Alboran Sea to the Levantine Sea. Five lessepsian species namely Erugosquilla massavensis, Syrnola fasciata, Plocamopherus ocellatus, Maritigrella fuscopunctata and Siganus javus have spread within 2025 to neighbouring MSFD areas. Another five are here reported as first country records [Polyandrocarpa zorritensis (Malta), Gonioinfradens giardi (Italy), Istiblennius meleagris (Egypt), Epinephelus fasciatus (Israel), Lophocladia trichoclados (Montenegro)]. Cladophora patentiramea has spread from the Levantine to the Aegean Sea, while Pinctada radiata has reached Granada, and Cádiz. The Atlantic fish Enchelycore anatina and Synodus synodus have expanded their distribution to Montenegro and Syria respectively. Three rare native species are reported for first time at country level, while a fourth (Mobula birostris) has made an appearance more than a century after its first Mediterranean record.

New records of introduced species in the Mediterranean Sea (December 2025) - MICHEL BARICHE; SHAHENAZ M. ABD ELLAH; OKAN AKYOL; EMAN SALEM ALFERGANI; ANDREA ALVITO; FIRAS ALSHAWY; IZDIHAR ALI AMMAR; ÉRICA CAROLINE BECKER; GIAMBATTISTA BELLO; DAMLA BETON; SENEM ÇAĞLAR; GIOVANNI CANDUCI; et al. (Mediterranean Marine Science, 2025)
New records of introduced species in the Mediterranean Sea (December 2025)